Structural behaviour of hybrid stainless steel stub columns under axial compression. (October 2020) - Lalthazuala, Ricky; Darunkumar Singh, Konjengbam
Abstract: Numerical study on structural performance of hybrid stainless steel stub columns are provided in this paper by utilizing finite element (FE) software, Abaqus. Two novel stainless steel grades were used viz., Lean duplex stainless steel (LDSS) and Duplex stainless steel (DSS) for hybrid stainless steel stub columns. The current investigation on hybrid stub columns consist of two configurations: (1) Hybrid stainless steel (HSS) stub column adopting DSS on the flanges and LDSS on the web; and (2) Hybrid stainless steel (HSS a ) stub column using DSS and LDSS on the web and flanges respectively. The numerical results are presented in terms of column capacity ( Pu ) and failure modes. As observed from the investigation, both flange thickness ( tf ) and flange width ( bf ) have more influence on the column capacity for HSS stub column as compared to HSS a stub column. On the other hand, increase in web thickness ( tw ) is found to provide an enhancement in column capacity for HSS a compared to HSS stub column, in contrast to the effect of tf and bf . In general, EN 1993-1-4 Class 3 limit for internal web is observed to be reliable for all stainless steel stub columns. Based on the FE results, new DSM formulation for HSS and HSS a stub columns was proposed based on modified DSM equation for carbon steel.